An adapted staining-destaining method to sort soft-bottom macrobenthos mixed with Posidonia oceanica fibers - DONNAY, A.; PELAPRAT, C.; LEJEUNE, P.; GOBERT, S. (Mediterranean Marine Science, 2013)
Sorting of soft-bottom macrobenthos entangled with Posidonia oceanica fibers is time-consuming and tedious because of the weak color contrast. This paper describes a staining-destaining technique that produces good contrast between soft-bottom macrobenthos and Posidonia oceanica fibers. The method has been tested on Corsican samples in oligotrophic areas characterized by small-size soft-bottom macrofauna. Our technique saves sorting time (-24%) and is simple to implement.